GRAPHICAL USER INTERFACE DALAM PERSPEKTIF PELINDUNGAN DESAIN INDUSTRI DI INDONESIA - Eko Saputro; Drajatno Widi Utomo; Achmad Syarief; Saputro, Eko (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2023)
GUI has become an integral component in various products and services amidst the rapid development of information and communication technology. Nonetheless, the legal landscape concerning protecting GUI designs, especially their non-physical aspects, is still evolving and may present challenges in ensuring sufficient intellectual property rights for designers. This study aims to explore non-physical design elements within the graphic user interface (GUI) design domain within the context of protecting industrial design in Indonesia. Employing a qualitative research model with a Grounded Theory approach, the researcher employed various systematic procedures to comprehend cases pertaining to GUI protection and how the application of graphical interface design principles can be protected within industrial design frameworks across different jurisdictions. Analyzing the gap (GAP) in the treatment of GUIs in intellectual property protection practices across various jurisdictions is a crucial aspect of the analysis aimed at establishing criteria and determining the novelty value of GUIs as objects of Industrial Design protection in Indonesia.Keywords: GUI, non-physical design, ndustrial design protection in Indonesia GUI telah menjadi komponen integral dari berbagai produk dan layanan ditengah pesatnya perkembangan teknologi informasi dan komunikasi. Namun, kerangka hukum untuk melindungi desain GUI, khususnya aspek non-fisik, masih terus berkembang dan dapat menghadirkan tantangan dalam memastikan hak kekayaan intelektual yang memadai bagi para desainer. Penelitian ini bertujuan untuk mengkaji objek desain non fisik dalam kategori desain antarmuka pengguna grafis (GUI) dalam konteks pelindungan desain industri di Indonesia. Penelitian ini menggunakan modus penelitian kualitatif dengan pendekatan Grounded Theory. Peneliti menggunakan sejumlah prosedur sistematis untuk memahami kasus-kasus yang berkaitan dengan pelindungan GUI (Desain Antarmuka Grafis) dan bagaimana penerapan konsep desain antarmuka grafis dapat dilindungi dalam rezim desain industri diberbagai yurisdiksi. Kesenjangan (GAP) perlakuan GUI dalam praktik pelindungan kekayaan intelelektual diberbagai yurisdiksi menjadi bagian penting yang dianalisis untuk mendapatkan kondisi ideal  dalam menetapkan kriteria dan menentukan nilai kebaruan GUI sebagai objek pelindungan Desain Industri di Indonesia. Kata kunci: GUI, desain non-fisik, pelindungan desain industri di Indonesia